Program Desa Caang: Penerapan Integrated Community Development (ICD) Menuju Masyarakat “Caang” - Heri Mohamad Tohari; Tig Julianto (Universitas Mathla'ul Anwar Banten, 2016)
In geothermal production area in Darajat Garut as well, from 41,239 families’ researched data, it was found that 9,995 families have yet to get electricity. In addition, health problems, malnutrition, low participation in education, literacy, etc. In another research which had involved 5,793 respondents in that area, a simple assessment, respondents were only ordered to write their names, just only 56,60% who could write their names and the rest 43,4% had total illiteracy and partly. This condition made the people increasingly closed and collapsed above the fertile area and abundant crops. Starting from the assumption of fulfilling electricity for that village, then launched an integrated self-contained village, with the name “Desa Caang (the bright village): Caang Listrikna (the bright electricity), Caang Otakna (the bright brain), Caang Pesakna (the bright pocket). This program consisted of free of charge of the electricity installation distribution for under privileged people, economic empowerment and education.